Strengthening the MSME Business Ecosystem Through Smart Economy–Based Optimization of BUMDes Institutions in Branjang Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to strengthen the business ecosystem of MSMEs in Branjang Village by optimizing the role of the Untung Makmur Village-Owned Enterprise (BUMDes) based on a Smart Economy framework. The implementation method integrates comprehensive capacity building and digital transformation rather than discrete training stages. Key activities included business management training, administrative digitization via the E-HAS application, assistance with business legality (NIB and Halal certification), and digital marketing optimization. The results indicate a significant increase in the managerial capacity of BUMDes and MSME operators. The program successfully established administrative efficiency, secured business legality, and enhanced product branding and market reach through e-commerce. Ultimately, this initiative demonstrates that integrating Smart Economy principles into BUMDes management acts as a vital catalyst for fostering a resilient, inclusive, and sustainable village economic ecosystem.